Elimination of excreted pathogens and effluent reuse issues; national framework for designing waste stabilization ponds - Faskol Adel S. (E3S Web of Conferences)
The main objective of this research is to establish a national framework to give requirements for effective design of waste stabilization ponds WSP for treating municipal wastewater in Libya, including specific information relating to removal (Faecal coliform bacteria and Helminth eggs). An empirical approach is the method for designing waste stabilization ponds WSP in Libya, where the raw municipal wastewater in study areas contains 108 Faecal coliform bacteria FC (MPN/100 mL) and 103 Helminth eggs egg/L. This research finds that in a hot-summer Mediterranean climate in Libya with an anaerobic pond, facultative pond, and first maturation pond where the hydraulic retention time HRT is 26.11 days, it produces 0.00 FC/100 ml and 0.00 egg/L. Moreover, in a hot semi-arid climate in Libya with an anaerobic pond, facultative pond, and first maturation pond where the hydraulic retention time HRT is 16.16 days, it produces 0.00 FC/100 ml and 0.00 egg/L. On the other hand, in a subtropical desert climate in Libya with an anaerobic pond, facultative pond, and first maturation pond where the hydraulic retention time HRT is 28.03 days, it produces 0.00 FC/100 ml and 0.00 egg/L.